THE PRINCIPLE OF THE BEST INTERESTS OF THE CHILD IN LAW ENFORCEMENT AGAINST CHILDREN WHO COMMIT RAPE - Cindy Shafira; Prija Djatmika; Nurini Aprilianda (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Handling rape cases involving children as perpetrators has become a complicated issue within the juvenile justice system in Indonesia. This crime not only causes deep psychological wounds to the victims, who are also still children, but also presents complex legal issues in the law enforcement process against the perpetrators who are legally minors. The principle of "the best interests of the child," as stipulated in” Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA)” and “the Convention on the Rights of the Child”, emphasizes that the approach to children in conflict with the law should focus more on rehabilitation and protection rather than mere punishment. This research aims to deeply explore the underlying considerations of judges in adjudicating cases of rape committed by children, using a case study from the Pasir Pengaraian District Court's verdicts. Through normative legal research methods with a case study approach, it was found that the Judge in adjudicating the case had prioritized the principle of "the best interests of the child." Disparities in court rulings result from the juvenile justice system's uneven practical implementation, notwithstanding its normative orientation toward a restorative justice paradigm that prioritizes rehabilitation. To guarantee a more uniform, equitable, and really child-centered justice system, this study emphasizes the necessity of harmonizing and standardizing the application of the "best interests of the child" principle across the entire legal procedure.